2012
DOI: 10.1177/0022022112468942
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Rosenberg Self-Esteem Scale

Abstract: Abstract:This study evaluated the factor structure of the Rosenberg Self-Esteem Scale (RSES) with a diverse sample of 1,248 European American, Latino, Armenian, and Iranian adolescents. Adolescents completed the 10-item RSES during school as part of a larger study on parental influences and academic outcomes. Findings suggested that method effects in the RSES are more strongly associated with negatively worded items across three diverse groups but also more pronounced among ethnic minority adolescents. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
69
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 25 publications
8
69
0
8
Order By: Relevance
“…It assesses global self‐esteem based on 10 items that are a mixture of positively and negatively worded items. However, there is an ongoing, heated debate regarding whether the positively and negatively worded items assess the same construct that affects the very meaning of self‐esteem (Marsh, ; Marsh, Scalas, & Nagengast, ; Owens, ; Supple, Su, Plunkett, Peterson, & Bush, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It assesses global self‐esteem based on 10 items that are a mixture of positively and negatively worded items. However, there is an ongoing, heated debate regarding whether the positively and negatively worded items assess the same construct that affects the very meaning of self‐esteem (Marsh, ; Marsh, Scalas, & Nagengast, ; Owens, ; Supple, Su, Plunkett, Peterson, & Bush, ).…”
Section: Introductionmentioning
confidence: 99%
“…When compared with positive self‐esteem, negative self‐esteem did indeed show differential patterns of association with theoretically related constructs (Farruggia, Chen, Greenberger, Dmitrieva, & Macek, ; Owens, ). For example, negative self‐esteem is more strongly related to depressive symptoms (Farruggia et al, ; Owens, ) and psychological control than positive self‐esteem (Supple et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically this disagreement centers on whether or not the scale assesses global self-esteem as one factor (as conceptualized by Rosenberg, 1965) based on a mixture of 10 positively and negatively worded items, or as two distinct constructs representing positive and negative aspects of self-esteem. Accordingly results of both exploratory and confirmatory factor analyses (EFA/CFA) on different versions of RSES (6, 7, and 10 items) across different populations have supported a one-factor, unidimensional solution (e.g., Shevlin, Bunting, and Lewis, 1995) and a two-factor solution representing positive and negative self-esteem (Ang, Neubronner, Oh, & Leong, 2006;Boduszek, Hyland, Dhingra, & Mallett, 2013;Quilty, Oakman, & Risko, 2006;Supple, Su, Plunkett, Peterson, & Bush, 2013).…”
mentioning
confidence: 95%
“…A current debate regarding the RSES centers on whether or not bidimensional findings demonstrate that the RSES assesses two substantively distinct elements related to self-esteem that are the result of method effects (Supple et al, 2013). In fact, these authors reported a two-factor solution for the RSES in adolescents and that the two factors were differentially predicted by parenting behaviors and academic motivation.…”
mentioning
confidence: 99%
“…Neither would it make sense to interpret the results of a test if its application in two contexts is associated with different measurement errors (Elosua, 2005). Both questions are contingent on checking factorial invariance (Byrne, 2008;Dimitrov, 2010;Elosua & Muñiz, 2010;Supple, Su, Plunkett, Peterson & Bush, 2012;Zecca et al, 2012). Van de Vijver and Leung (1997) proposed three forms of factorial equivalence: configural invariance, in which the underlying psychological process is the same in the different groups since all the factors are shaped by the same items; metric invariance, in which the scaling metrics are the same; and scalar invariance, in which the origin of the scale is also the same for the different groups.…”
Section: Introductionmentioning
confidence: 99%